2016
DOI: 10.1039/c5ob02356d
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro selectivity of an acyclic cucurbit[n]uril molecular container towards neuromuscular blocking agents relative to commonly used drugs

Abstract: An acyclic cucurbit[n]uril (CB[n]) based molecular container (2, a.k.a. Calabadion 2) binds to both amino-steroidal and benzylisoquinolinium type neuromuscular blocking agents (NMBAs) in vitro, and reverses the effect of these drugs in vivo displaying faster recovery times than placebo and the γ-cyclodextrin (CD) based and clinically used reversal agent Sugammadex. In this study we have assessed the potential for other drugs commonly used during and after surgery (e.g. antibiotics, antihistamines, and antiarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Among Calabadions 1 and 2 and CB[7], CB[7] displays the highest levels of affinity and selectivity toward the drugs of abuse panel. However, the affinity and selectivity of 1 and 2 seen herein and also documented in the context of neuromuscular block reversal, [15] is substantial and suggests that 1 and 2 could serve as core scaffolds for further structural optimization. We are mindful of the fact that metabolites of amino acids, especially phenylalanine, will likely display similar binding affinity toward Calabadion 2 as methamphetamine does which could compromise in vivo efficacy.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Among Calabadions 1 and 2 and CB[7], CB[7] displays the highest levels of affinity and selectivity toward the drugs of abuse panel. However, the affinity and selectivity of 1 and 2 seen herein and also documented in the context of neuromuscular block reversal, [15] is substantial and suggests that 1 and 2 could serve as core scaffolds for further structural optimization. We are mindful of the fact that metabolites of amino acids, especially phenylalanine, will likely display similar binding affinity toward Calabadion 2 as methamphetamine does which could compromise in vivo efficacy.…”
mentioning
confidence: 77%
“…[11, 12] Recently, Isaacs and Eikermann have shown that acyclic CB[n]-type molecular containers (Calabadion 1 and 2 ) bind strongly to rocuronium, vecuronium and cisatracurium in vitro and function as in vivo reversal agents in rats. [13, 14, 15] Given that CB[n]-type molecular containers generally possess a high affinity toward hydrophobic cations and that many drugs of abuse fall into this class of compounds, we decided to evaluate the potential of molecular containers as agents for the in vivo reversal of the biological effects of drugs of abuse by the PK strategy. In particular, the use of molecular containers to treat intoxication with drugs of abuse – as opposed to addiction where long circulation times would be needed – seems most promising.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We performed binding studies of 27 toward 27 drugs commonly used during or after surgery. [45] Then, we performed computer simulations of a simple equilibrium binding model that takes into account the binding constants of 27 toward NMBA and competing drug, the estimated binding constant of NMBA toward the biological receptor, and the plasma concentrations. Under the constraints of the simulations, we find that none of the 27 drugs studied results in significant displacement interactions.…”
Section: Acyclic Cb[n]-type Receptorsmentioning
confidence: 99%
“…A stronger interaction between viologen 45 and CB [7] is also measured in aqueous solution compared to DMSO (> 8 3 10 5 M À1 vs. 3.4 3 10 M À1 in the case of R = CH 3 ). [93][94][95][96][97][98] However, as described above, most guest/CB[n] exchanges take place within a few seconds or much less, unless guests with fine-tuned obstacles are designed to slow down the process (see section 4.3). [87] One could also argue that DMSO is a much better hydrogen bond acceptor than water (Hunter assigned hydrogen bond donor parameters a and hydrogen bond acceptor parameters b to a series of solvents; [88,89] the b parameter for water and DMSO are 4.5 and 8.9, respectively).…”
Section: Threading and Related Exchangesmentioning
confidence: 99%